2019
DOI: 10.19044/esj.2019.v15n15p165
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation Physico-Chimique des Sols des Vallées Agricoles de la Commune de Ziguinchor au Sénégal

Abstract: Despite the importance of urban agriculture as a strategic axe of resilience to poverty, Ziguinchor's urban agriculture is not well considered by the municipalty autorities and suffers from spatial and soil transformations. The study aims to establish a frame of reference for soil physicochemical characteristics of the agricultural valleys of Ziguinchor's city. For that, 180 soil core samples were collected on the horizon [0-20] cm. They were made up of 12 composite samples analyzed at the Senegal National Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Soil pH plays an important role in the availability of nutrients for crops (Dinon and Gerstmans, 2008). This acidification of cropping areas especially at valley level has been raised by several authors (Diallo et al, 2015;Dasylva et al, 2019). It is caused by rainfall deficit, groundwater recharge, sulphide oxidation (Duchaufour, 1983;FAO, 1998).…”
Section: Gradient Of Acidity Analysis (Ph) In the Bakoum Valley In 20mentioning
confidence: 98%
See 1 more Smart Citation
“…Soil pH plays an important role in the availability of nutrients for crops (Dinon and Gerstmans, 2008). This acidification of cropping areas especially at valley level has been raised by several authors (Diallo et al, 2015;Dasylva et al, 2019). It is caused by rainfall deficit, groundwater recharge, sulphide oxidation (Duchaufour, 1983;FAO, 1998).…”
Section: Gradient Of Acidity Analysis (Ph) In the Bakoum Valley In 20mentioning
confidence: 98%
“…It is also the irresponsibility of the beneficiaries. The hydro-agricultural developments that have been carried out in this area have not often met the objective set because of the lack of collaboration of the populations (Dasylva et al, 2019). During the exploratory mission to the Bakoum Valley, the chief of the village of Badiandiang Diola informed that the locks of the structure that regulate the water upstream were stolen by the villagers themselves.…”
Section: Gradient Of Acidity Analysis (Ph) In the Bakoum Valley In 20mentioning
confidence: 99%
“…Consequently, crop yields and the smooth running of human agropastoral activities are compromised. Soil leaching and the phenomena of drought, rainfall disturbances, shifting and shortening of the rainy season alone weaken the structure and physicochemical composition of soils [20]. Because coarse elements (sand) are dominant in these soils, they are poor reservoirs of water that can be used by plants.…”
Section: Textural and Granulometric Characteristics Of Watershed Soilsmentioning
confidence: 99%
“…However, the profound change in the physical properties of the soil can significantly negatively affect soil productivity and hence crop yields. The studies by [20] in the city of Ziguinchor in Senegal, have shown that the splash effect of the intense rains often recorded favors the stripping of the soil, the transport of sandy particles by runoff and silting up of rice fields. A good structure of the topsoil layers is essential in agricultural activities.…”
Section: Textural and Granulometric Characteristics Of Watershed Soilsmentioning
confidence: 99%
See 1 more Smart Citation